A Systematic Review on Clinical Safety and Efficacy of Vancomycin Loading Dose in Critically Ill Patients - Haseeb, Abdul; Alqurashi, Mayyasah Khalid; Althaqafi, Areej Sultan; Alsharif, Jumana Majdi; Faidah, Hani Saleh; Bushyah, Mashael; Alotaibi, Amal F.; Elrggal, Mahmoud Essam; Mahrous, Ahmad Jamal; Abuhussain, Safa S. Almarzoky; Obaid, Najla A.; Algethamy, Manal; et al. (Antibiotics (Basel), 2022)
Background: The clinical significance of utilizing a vancomycin loading dose in critically ill patients remains unclear. Objective: The main aim of this systematic review is to evaluate the clinical safety and efficacy of the vancomycin loading dose in critically ill patients. Methods: We performed a systematic review using PRISMA guidelines. PubMed, the Web of Science, MEDLINE, Scopus, Google Scholar, the Saudi Digital Library and other databases were searched. Studies that reported clinical outcomes among patients receiving the vancomycin LD were considered eligible. Data for this study were collected using PubMed, the Web of Science, MEDLINE, Scopus, Google Scholar and the Saudi Digital Library using the following terms: “vancomycin”, “safety”, “efficacy” and “loading dose” combined with the Boolean operator “AND” or “OR”. Results: A total of 17 articles, including 2 RCTs, 11 retrospective cohorts and 4 other studies, met the inclusion/exclusion criteria out of a total 1189 studies. Patients had different clinical characteristics representing a heterogenous group, including patients in critical condition, with renal impairment, sepsis, MRSA infection and hospitalized patients for hemodialysis or in the emergency department. Conclusions: The study shows that the target therapeutic level is achieved more easily among patients receiving a weight-based LD as compared to patients received the usual dose without an increased risk of new-onset adverse drug reactions.